2020
DOI: 10.1371/journal.pone.0227987
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and gene loss occur simultaneously during bacterial horizontal gene transfer

Abstract: Bacteria can acquire new genes by incorporating environmental DNA into their genomes, yet genome sizes stay relatively constant. In nature, gene acquisition is a rare event so it is difficult to observe. However, the Caulobacter crescentus CB2A genome contains 114 insertions of genetic material from the closely-related NA1000 strain, providing a unique opportunity to analyze the horizontal transfer of genetic material. Analyses of these insertions led to a new model that involves preferential recombination at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Indeed, HGT provides a driving force for bacterial evolution, increasing bacterial survival, adjustment rate in the harshest environments, and pathogenicity [2][3][4]. Current knowledge of HGT is based on three widely described mechanisms for the exchange of genetic material between bacteria: transformation, conjugation and transduction [5][6][7]. Transformation involves the natural uptake of naked DNA from an extracellular environment; this phenomenon occurs when cells are in a physiological state of competence, regulated by 20-50 proteins [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, HGT provides a driving force for bacterial evolution, increasing bacterial survival, adjustment rate in the harshest environments, and pathogenicity [2][3][4]. Current knowledge of HGT is based on three widely described mechanisms for the exchange of genetic material between bacteria: transformation, conjugation and transduction [5][6][7]. Transformation involves the natural uptake of naked DNA from an extracellular environment; this phenomenon occurs when cells are in a physiological state of competence, regulated by 20-50 proteins [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, biased gene conversion could only occur during relatively rare recombination events [19] while eukaryotic recombination occurs multiple times during every round of meiosis. Furthermore, we have shown that biased gene conversion did not occur during more than 100 distinct recombination events analyzed in the high GC genomes of C. vibrioides [25]. Thus, biased gene conversion does not appear to occur during recombination events in the high GC genomes of this bacterial species.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, we have shown that biased gene conversion did not occur during more than 100 distinct recombination events analyzed in the high GC genomes of C . vibrioides [ 25 ]. Thus, biased gene conversion does not appear to occur during recombination events in the high GC genomes of this bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…However, biased gene conversion could only occur during relatively rare recombination events [11] while eukaryotic recombination occurs multiple times during every round of meiosis. Furthermore, we have shown that biased gene conversion did not occur during more than 100 distinct recombination events analyzed in the high GC genomes of C. vibrioides [15]. Thus, biased gene conversion does not appear to occur during recombination events in the high GC genomes of this bacterial species.…”
Section: Introductionmentioning
confidence: 78%